Living the past in the present: a reconstruction of the memories of war and violence of former Congolese soldiers living in South Africa - Lakika, Dostin Mulopo (My University, 2019)
This study sought to explore and understand the memories and lived experiences of former soldiers from the time they joined the army until their exit and post-army life in South Africa. The study highlights the significance of the contexts in which former soldiers recount their military experiences as forced migrants in a different country. Drawing on empirical data generated from interviews with former Congolese soldiers in Johannesburg, this study examined the socio-environmental impact on former soldiers’ remembering/forgetting war and violence as refugees in a different context - South Africa. Based on fieldwork in the city of Johannesburg, South Africa, the study uses traditional ethnographic methods. Narrative interviews and participant observation were appropriately used to examine the lived realities of twenty-one former soldiers living as refugees in South Africa. The study employed thematic analysis to understand the various discourses of militarisation in different fields. The study conceptualised the socio-environmental as Bourdieu’s concept of fields, exploring the lives of former soldiers in both the DRC field and South African field. The field is a social space defining the boundaries of actions and offering the conditions that shape those actions. I am using the term field to talk about military activities in the Congo bearing in mind that this military field has internal connections with the Congolese society which differ from the South Africa context. One of the main objectives of this study was to understand the impact of the social space offered by South Africa on former soldiers’ understanding and implementing of military ideology or principles and practices which are based on the violence. This study’s goal was to explore if former soldiers’ conception of war and violence remained un/changed after moving from one context to another, whether military behaviour, attitude or principles continued to influence their lives in South Africa and more importantly when and how they drew on the military discourse in their new country. Using Bourdieu’s concepts, this study was also concerned about military principles/practices former soldiers did habitualise or de-habitualise in their postmilitary lived experiences in South Africa. Here, I argue that military identity, as constructed, is hugely spatialized. Therefore, this study is about exploring military habitus outside the military field. Overall, this study found that the motivation to join the army for many participants was informed by the search for meaningful masculinity which incorporated dimensions of economic success, violence through revenge or defence and their role in an emerging nation. This masculinity was constructed in relation to coloniality and ongoing colonial hierarchies. Military identity or military violence is inextricably linked to the specific field. The military identity in the DRC field, for instance, included the creation of ‘rights’ to which soldiers had access. These rights became, to use Bourdieu’s term, ‘doxalised’. Conceptualised as a patriarchal institution, the army was also defined as a place of discipline and order which are viewed as products of violence. Soldiers learnt to obey without questioning the authority of their superiors. Following the superiors’ commands is one of the tenets of military training that informs the transition from civilian to soldier. On the other hand, soldiers echo this patriarchal conception when they deal with civilians, expecting them to obey and surrender without resistance. However, in the South African context, this study found that military habitus of former soldiers was being constituted and constituting, constantly negotiated—that is constructed/ing, reconstructed/ing and maintained/ing. This study found that habitus can be acquired, claimed and even dismissed and more importantly, migration significantly impacts on the identities of former soldiers. I argue that while some of their military practices have become habitualised, this habitualisation is complex and altered by multiple realities of the host society. The results of this study combined with the rich literature reviewed provide, therefore, a significant theoretical contribution to the understanding of the influence of the field in the definition of military identity, military violence in the context of mobility. The study also offers great contribution to the current concepts developed by Bourdieu which do not account for the capital that ex-soldiers deploy in the migratory context that acts as a new field. I therefore argue that Bourdieu’s five concepts of field, capital, practice, habitus and symbolic violence should be reconceptualised to add military capital as a new concept of capital particularly when applying these concepts in the contexts of former military personnel mobility.
A thesis submitted to the Faculty of Humanities in fulfilment of the requirements for the Degree of Doctor of Philosophy, April 2019